2009
DOI: 10.1021/bm900660b
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Living Bifidobacteria in Ultrathin PVOH Electrospun Fibers

Abstract: This study shows the application of the electrospinning technique as a viable method for the encapsulation and stabilization of bifidobacterial strains. Poly(vinyl alcohol) (PVOH) was used as the encapsulating material because it is generally recognized as safe (GRAS), has a high oxygen barrier when dry, and is water soluble, hence allowing easy recovery of the bacteria for viability testing. A coaxial setup was used for encapsulation, and the so-obtained electrospun fibers had a mean diameter of ca. 150 nm. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(136 citation statements)
references
References 37 publications
1
134
0
1
Order By: Relevance
“…Dheraprasart et al (30), however, reported a slight increase in fiber diameter when gelatin solutions were electrospun with nisin, but the increase was not statistically significant. Various molecules and living organisms have been electrospun into a variety of natural and synthetic fibers, as well as blends thereof, including antibiotics, growth factors, antimicrobial peptides, and silver nanoparticles, as well as living bacteria (31,(36)(37)(38)(39)(40)(41)(42). Addition of molecules to a solution before electrospinning may alter the conductivity, surface tension, and possibly the viscosity of the solution and thus influence the morphology and diameter of fibers formed during electrospinning.…”
Section: Discussionmentioning
confidence: 99%
“…Dheraprasart et al (30), however, reported a slight increase in fiber diameter when gelatin solutions were electrospun with nisin, but the increase was not statistically significant. Various molecules and living organisms have been electrospun into a variety of natural and synthetic fibers, as well as blends thereof, including antibiotics, growth factors, antimicrobial peptides, and silver nanoparticles, as well as living bacteria (31,(36)(37)(38)(39)(40)(41)(42). Addition of molecules to a solution before electrospinning may alter the conductivity, surface tension, and possibly the viscosity of the solution and thus influence the morphology and diameter of fibers formed during electrospinning.…”
Section: Discussionmentioning
confidence: 99%
“…PVA as a nanofiber matrix was chosen since PVA is a suitable polymer type for food packaging applications shown in the literature by incorporating different molecules or bacteria into PVA films [30] and fibers [5,31] due to its high tensile strength, flexibility, high oxygen and barrier properties. Free AITC and inclusion complex of AITC with ␤-CD (AITC/␤-CD-IC) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Salalha et al [24] showed that Escherichia coli and Staphylococcus albus remained viable after electrospinning process and retained their viability in polyvinyl alcohol (PVA) matrix for at least 3 months when the bacteria-containing electrospun webs were stored at -20 and -55°C. Lopez-Rubio et al [25] incorporated living probiotic bacteria (B. animalis Bb12) into PVA nanofibers applying co-electrospinning and the cells remained viable after 40 days at room temperature and 130 days at 4 and -20°C under refrigeration. Henceforth they encapsulated B. animalis Bb12 into protein-and carbohydrate-based microcapsules using electrospraying [26].…”
mentioning
confidence: 99%